A model of trust - Gabriele Bellucci (Games, 2022)
Trust is central to a large variety of social interactions. Different research fields have empirically and theoretically investigated trust, observing trusting behaviors in different situations and pinpointing their different components and constituents. However, a unifying, computational formalization of those diverse components and constituents of trust is still lacking. Previous work has mainly used computational models borrowed from other fields and developed for other purposes to explain trusting behaviors in empirical paradigms. Here, I computationally formalize verbal models of trust in a simple model (i.e., vulnerability model) that combines current and prospective action values with beliefs and expectancies about a partner's behavior. By using the classic investment game (IG)-an economic game thought to capture some important features of trusting behaviors in social interactions-I show how variations of a single parameter of the vulnerability model generates behaviors that can be interpreted as different 'trust attitudes'. I then show how these behavioral patterns change as a function of an individual's loss aversion and expectations of the partner's behavior. I finally show how the vulnerability model can be easily extended in a novel IG paradigm to investigate inferences on different traits of a partner. In particular, I will focus on benevolence and competence-two character traits that have previously been described as determinants of trustworthiness impressions central to trust. The vulnerability model can be employed as is or as a utility function within more complex Bayesian frameworks to fit participants' behavior in different social environments where actions are associated with subjective values and weighted by individual beliefs about others' behaviors. Hence, the vulnerability model provides an important building block for future theoretical and empirical work across a variety of research fields.
Keywords: 330; benevolence; competence; computational modeling; investment game; loss aversion; trust; trust game; trustworthiness